Luminosity functions using new radio surveys - Peters, J (2019)
Galaxy evolution at radio wavelengths is often measured using luminosity functions which are commonly based on the luminosity (L) and redshift (z) of individual sources as well as the overall distribution for a sample. However, an important factor when K-correcting radio sources to their rest-frame luminosity is the spectral index (α). This is often assumed to be a constant value for the entire sample. In reality, there is a distributioninαwhich affects the rate at which sources drop below the flux limit of thesurvey. If not accounted for, the differing rates at which sources become unobservable can be mistaken as a genuine decline in source numbers and affect the evolution of the radio luminosity function (RLF).